2007
DOI: 10.1186/1471-2407-7-174
|View full text |Cite
|
Sign up to set email alerts
|

Ductal carcinoma in situ of the breast (DCIS) with heterogeneity of nuclear grade: prognostic effects of quantitative nuclear assessment

Abstract: Background: Previously, 50% of patients with breast ductal carcinoma in situ (DCIS) had more than one nuclear grade, and neither worst nor predominant nuclear grade was significantly associated with development of invasive carcinoma. Here, we used image analysis in addition to histologic evaluation to determine if quantification of nuclear features could provide additional prognostic information and hence impact prognostic assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 34 publications
(37 reference statements)
0
37
0
1
Order By: Relevance
“…DCIS is by definition not associated with stromal invasion but its biological potentials of invasion have been always in dispute. (12,13) DCIS is also classified into several types based on its potential to recur or develop into invasive carcinoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DCIS is by definition not associated with stromal invasion but its biological potentials of invasion have been always in dispute. (12,13) DCIS is also classified into several types based on its potential to recur or develop into invasive carcinoma.…”
mentioning
confidence: 99%
“…DCIS is by definition not associated with stromal invasion but its biological potentials of invasion have been always in dispute. (12,13) DCIS is also classified into several types based on its potential to recur or develop into invasive carcinoma. (12) The correlation between these phenotypes and the status of neovascularization of each cases, however, has been little examined in DCIS.…”
mentioning
confidence: 99%
“…They showed that almost 50% of samples exhibit diversity of grade, be it different grade in the same duct, different grade in different ducts in the same area, or different grades in different areas [6]. This recognition of diversity is not formally acknowledged in current pathological reporting schemes, but it may have clinical significance, although a study using the worst or the predominant grade in the Van Nuys system did not show association with recurrence or development of invasive disease in those patients with heterogeneity [10].…”
Section: Abstract Dcis · Linear Progression · Parallel Progression ·mentioning
confidence: 87%
“…89 And nuclear densitometric features were significantly associated with nuclear grading. 90 In addition, the spatial arrangement of cell nuclei is important in distinguishing between differentiation degrees. Basavanhally et al 89 presented a multi-field-ofview method to integrate nuclear texture feature and spatial-arrangement feature for grading.…”
Section: Quantify Epithelial Features On Prognosismentioning
confidence: 99%